Methodology of Teaching Sport - Hakimova Nargiza (European Science Publishing, 2024)
Its purpose is to increase the level of development of motor qualities and functional capabilities of the athlete's body for this stage of training in strict accordance with the requirements of the chosen sport. This means, first of all, the development of basic physical qualities: strength, speed, endurance and flexibility. At the same time, one should not forget about the possibilities of accompaniment to improve the coordination of movements, their expressiveness, dexterity and accuracy.